Consumers’ Marketing Channel Choice and the Impact on Logistics and Operations: A Systematic Literature Review of the Fresh Food and Grocery Sector - Hassan Alkhiyami; Laoucine Kerbache; Majed Hadid (Logistics, 2024)
Background: Diverse marketing channels have been developed with the advent of digitalization. In the fresh food and grocery retail sector, consumers may have a large choice of channels to shop from. In this case, an analysis of their behavior is crucial for retailers. Therefore, the present paper provides a state-of-the-art review of existing papers dealing with consumers’ channel choice when buying groceries. Methods: A systematic literature review (SLR) is performed following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) procedure, identifying 36 research papers published in the last decade. Results: The results present the principal methodologies adopted by the analyzed research papers to address this topic, along with the various channels available to consumers to date. Other important outcomes of this review include the main variables that can affect consumer choice when deciding between the available channels and the limitations of the analyzed papers, along with suggestions for future research directions to address these limitations. Conclusions: This paper discusses the essential effects of consumers’ channel choice on the logistics and operation services of grocery retailers. It also provides an integrative framework linking the influencing factors of consumer choice with outcomes directly impacting grocery retailers’ logistics services.